ANALISIS PERILAKU KONSUMEN BERAS ORGANIK DI KABUPATEN JEMBER - Titin Agustina (University of Jember, 2011)
Food is an essential commodities and strategic. Rice is one commodity food that has an important role, both in terms of producers, consumers, government, the community and the environment in general. With increasing population, increasing levels of education and income per capita then the need for rice in particular food consumption also increased. The enthusiasm of the public to consume organic rice is also expected continues to increase along with the awareness of people to live healthy. Research in Consumer Behavior Analysis of Organic Rice in Jember conducted in order to determine: (1). Factors that influence the behavior of consumers in the purchase of organic rice in Jember, (2). Is there a relationship between level of education and income levels of consumers with consumer response to quality attributes of rice in the purchase of organic rice in Jember. This study was conducted in Jember with sampling and identification method in the field. The results showed: (1). the factors that influence consumer behaviour in purchasing organic rice in Jember is the quality factor (texture, grain, color, taste), promotion factor (friend information, leaflets, sellers, packaging), health factors (nutrition and nourishment), factor of safety of consuming (where to buy, certification, pesticide residues) and factor of prices (2). There is no real relationship between the levels of education of consumers with consumer response to quality attributes of rice in the purchase of organic rice in Jember (3). There is no real relationship between the levels of income the consumer response to the quality attributes of rice in the purchase of organic rice in Jember. Key words : Organic Rice, Consumer Behavior, Quality Attributes of Rice